A Benchmark Test Suite for the Electric Capacitated Vehicle Routing Problem - Mavrovouniotis, Michalis; Menelaou, Charalambos; Timotheou, Stelios; Ellinas, Georgios; Panayiotou, Christos; Polycarpou, Marios M. (My University, 2020)
Severa1 logistic companies started utilizing electric vehicles (EVs) in their daily operations to reduce greenhouse gas pollution. However, the limited driving range of EVs may require visits to recharging stations during their operation. These potential visits have to be addressed, avoiding unnecessary long detours. We formulate the electric capacitated vehicle routing problem (E-CVRP), which incorporates the possibility of EVs visiting a recharging station while satisfying the delivery demands of customers. The energy consumption of the EVs is proportional to their cargo load which is an important constraint in real-world logistics applications. A new set of benchmark instances is proposed for the E-CVRP. As solution methods to these new benchmarks, we apply the ant colony optimization metaheuristic method and an exact method. Experimental results on the ECVRP demonstrate the high complexity of the problem and the efficiency of the applied metaheuristic solution method.
Keywords: benchmark instance; capacitated vehicle routing problem; Electric vehicle